Tree Biomass and Carbon Sequestration of Three Mangrove Species Planted in Bogachattor Forest Beat in the Chattogram Coast, Bangladesh (The Chittagong University Journal of Science, 2023)
The global climate is changing significantly due to deforestation, forest degradation and burning of fossil fuels. Afforesting along the coastal belt, Bangladesh may play a significant role in mitigating global climate change. This study quantified the tree-biomass and carbon mass in the Bogachattor forest beat of the Sitakunda forest range under the Chattogram coastal forest division. The study estimated that the total biomass of Sonneratia apetala, Avicennia officinalis, and Excoecaria agallocha were 432.61±82.02, 251.15±23.71, and 59.08±5.04 t ha- 1, respectively, with the mean annual increment of 21.63±4.10, 12.56±1.19, and 2.95±0.25 t ha-1 y-1, respectively. Furthermore, the total carbon mass were 216.31±41.01, 125.58±11.85, and 29.54±2.52 t C ha-1 for S. apetala, A. officinalis, and E. agallocha, respectively, with the mean annual increment of 10.82±2.05, 6.28±0.59, and 1.48±0.13 t C ha-1 y-1, respectively. Overall, the findings indicated that S. apetala, A. officinalis, and E. agallocha-based afforestation has the potential to mitigate climate change. The findings can be helpful for researchers and policymakers on the national and global scale to mitigate climate change.The Chittagong Univ. J. Sci. 44(1): 33-50, 2022